Public health challenges in the Cuzco region: a decade of anemia in vulnerable populations applying data mining - Rubio Paucar, Inoc; Andrade-Arenas, Laberiano (Institute of Advanced Engineering and Science, 2025)
The objective of the research is to carry out an exhaustive analysis of anemia in the province of Cusco using the Rapid Miner Studio tool that allows an analysis of the number of most concurrent cases in each district of the province of Cusco. Different sources of information were consulted to take as a reference the impact of the disease in different parts of the world. Likewise, information was introduced about how information technologies manifest positive responses in certain diseases around the world. The knowledge discovery in databases (KDD) methodology was used, which consists of several phases proposed in the project, such as data selection, data preprocessing, data mining and evaluation of results. Consequently, this research will help to recognize the most abundant cases in the districts of the province of Cusco. The results obtained were that 348 confirmed cases of anemia occurred in the district of Espinar, being the most affected district. Finally, it was concluded that in different provinces, not only in Cusco, there is a high prevalence of the disease due to factors associated with its treatment.